BRAF Status in Papillary Microcarcinomas of the Thyroid Gland: a Brief Review - Ieni, Antonio; Vita, Roberto; Cardia, Roberta; Giuffrè, Giuseppe; Benvenga, Salvatore; Tuccari, Giovanni (Current Molecular Medicine, 2019)
Papillary thyroid microcarcinoma (PTMC) is defined by the World Health Organization as papillary cancer measuring 10 mm or less in diameter. Generally, PTMC shows an indolent clinical behavior with a good prognosis, although a minority of PTMC is characterized by an aggressive course. However, efforts to identify this aggressive subset of PTMC after surgery remain inconclusive. Several oncogenic pathways have been identified in thyroid cancer and have been applied translationally to improve prognosis and clinical management. In particular, the BRAFV600E mutation was found more frequently in large, aggressive, recurrent and advanced tumors. We aimed at reviewing studies on BRAFV600E mutation as a prognostic factor in PTMC.
Keywords: mutation